2020
DOI: 10.1039/d0ra03790g
|View full text |Cite
|
Sign up to set email alerts
|

Natural deep eutectic solvent supported targeted solid–liquid polymer carrier for breast cancer therapy

Abstract: Solid–liquid nanocarriers (SLNs) are at the front of the rapidly emerging field of medicinal applications with a potential role in the delivery of bioactive agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…A new type of solid-lipid nanoparticle (SLN) of NADES and biotin-conjugated lysine-polyethylene glycol copolymer were prepared for paclitaxel (PTX) and 7-hydroxycoumarin (7-HC) and characterized for particle size, surface morphology, functional groups, and thermal stability. Both the drug-loaded novel SLN systems exhibited strong anticancer properties of drug molecules in cancer treatment [ 68 ].…”
Section: Pharmaceutical Applications Of Thedesmentioning
confidence: 99%
“…A new type of solid-lipid nanoparticle (SLN) of NADES and biotin-conjugated lysine-polyethylene glycol copolymer were prepared for paclitaxel (PTX) and 7-hydroxycoumarin (7-HC) and characterized for particle size, surface morphology, functional groups, and thermal stability. Both the drug-loaded novel SLN systems exhibited strong anticancer properties of drug molecules in cancer treatment [ 68 ].…”
Section: Pharmaceutical Applications Of Thedesmentioning
confidence: 99%
“…Several studies have demonstrated the role of TheDESs in the treatment of dermatological, infectious and metabolic related diseases, such as wound healing, diabetes mellitus, and atherosclerosis [119,120] . Moreover, some eutectic systems showed a cytotoxic effect against a wide range of cancer cell lines [121,122] …”
Section: Role Of Deep Eutectic Solvents In Drug Engineeringmentioning
confidence: 99%
“…[119,120] Moreover, some eutectic systems showed a cytotoxic effect against a wide range of cancer cell lines. [121,122] The APIs must efficiently and specifically reach the site of action to achieve the desired therapeutic effect. However, the obstacles to drug delivery come in different forms and involve poor biopharmaceutical properties of the APIs such as chemical instability, low solubility, low permeability, and rapid metabolism and elimination from the body.…”
Section: Role Of Deep Eutectic Solvents In Drug Engineeringmentioning
confidence: 99%
“…They are mostly made of synthetic polymers and not liquid-based carriers, which sometimes compromises certain uses [54]. However, researchers are now exploring new carrier systems using ILs and DESs, although these have limitations, such as thermal instability, low drug loading levels, and low drug release and solubility [61].…”
Section: Small But Mighty: How Nanocarriers Are Revolutionizing Drug ...mentioning
confidence: 99%